2015
DOI: 10.1111/acer.12794
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization and Tolerance Following Repeated Exposure to Caffeine and Alcohol in Mice

Abstract: Introduction Energy drinks are popular mixers with alcohol. While energy drinks contain many ingredients, caffeine is an important pharmacologically active component and is generally present in larger amounts than in other caffeinated beverages. In these studies, we investigated the hypothesis that caffeine would influence the effects of alcohol (ethanol) on conditioned taste aversion, ataxia and locomotor activity after repeated exposure. Methods Four groups of mice were exposed by oral gavage twice daily t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 64 publications
(94 reference statements)
2
17
0
Order By: Relevance
“…Thus, the risks of drinking alcohol may be higher with consumption of AmED when compared to alcohol alone because the perceived stimulation is enhanced with an energy drink mixer. Given the importance of drug‐induced stimulation, it is notable that findings from several animal studies from different laboratories have reported that locomotor stimulation changes are enhanced for alcohol caffeine combinations when compared to either drug alone (Fritz et al., ; Hilbert et al., ; May et al., ). In one study, it was observed that binge consumption of alcohol by both adolescent and adult mice increased with caffeine, but only the adolescent mice exhibited robust locomotor stimulant responses to alcohol caffeine combinations (Fritz et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the risks of drinking alcohol may be higher with consumption of AmED when compared to alcohol alone because the perceived stimulation is enhanced with an energy drink mixer. Given the importance of drug‐induced stimulation, it is notable that findings from several animal studies from different laboratories have reported that locomotor stimulation changes are enhanced for alcohol caffeine combinations when compared to either drug alone (Fritz et al., ; Hilbert et al., ; May et al., ). In one study, it was observed that binge consumption of alcohol by both adolescent and adult mice increased with caffeine, but only the adolescent mice exhibited robust locomotor stimulant responses to alcohol caffeine combinations (Fritz et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments in mice have provided strong evidence for this hypothesis, showing that combination of caffeine and alcohol produce a stronger locomotor activity than either drug administered alone (Hilbert et al, 2013). The same research group recently reported that when given by oral gavage, repeated co-exposure to alcohol and caffeine produces a much larger effect than repeated exposure to either drug alone (May et al 2015). Under conditions of chronic alcohol intake (alcohol use disorder), in contrast to the acute situation, there is a reduced adenosine tone.…”
Section: The Real Danger: Caffeine Potentiates the Addictive And Toximentioning
confidence: 99%
“…In contrast, most animal studies have investigated the health impact of mixing alcohol with the believed key psychoactive component of energy drinks, caffeine. For instance, it has been demonstrated in mice that alcohol mixed with caffeine causes an approximately fourfold increase in locomotion compared with orally administered alcohol or caffeine alone (May, Haun, & Griffin ). Similar locomotor results were recently observed in adolescent mice when they were allowed to voluntarily consume alcohol, caffeine or its combination in a limited‐access binge‐like alcohol drinking paradigm (Fritz et al .…”
Section: Introductionmentioning
confidence: 99%